Compatibility study of rosmarinic acid with excipients used in pharmaceutical solid dosage forms using thermal and non-thermal techniques - Kleyton Santos Veras; Flávia Nathiely Silveira Fachel; Vanessa Pittol; Keth Ribeiro Garcia; Valquíria Linck Bassani; Venina dos Santos; Amélia Teresinha Henriques; Helder Ferreira Teixeira; Letícia Scherer Koester (Elsevier, 2019)
Rosmarinic acid (RA) is a phenolic compound that presents well-documented anti-inflammatory, antioxidant and antitumor activities, and based on its pharmacological potential and poor bioavailability, several solid dosage forms have been developed to RA delivery. Therefore, in literature, there are no reports about RA compatibility with excipients. In this regard, the aim of the present study was to evaluate, for the first time, the compatibility of RA with excipients commonly used in solid dosage forms at a 1:1 (RA:excipient) ratio using differential scanning calorimetry (DSC), thermogravimetry (TG), Fourier-transform infrared (FTIR), solid-state nuclear magnetic resonance (ssNMR), and isothermal stress testing (IST) coupled with liquid chromatography (LC). The excipients selected were hydroxypropyl methylcellulose (HPMC), microcrystalline cellulose (MCC), lactose monohydrate (LAC), polyvinylpyrrolidone (PVP), talc (TALC), croscarmellose sodium (CCS), and magnesium stearate (MgSTE). According to DSC results, physical interactions were found between RA and HPMC, LAC, CCS, and MgSTE. The TG analyses confirmed the physical interactions and suggested chemical incompatibility. FTIR revealed physical interaction of RA with TALC and MgSTE and the ssNMR confirmed the physical interaction showed by FTIR and excluded the presence of chemical incompatibility. By IST, the greatest loss of RA content was found to CCS and MgSTE (>15%), demonstrating chemical incompatibilities with RA. High temperatures used in DSC and TG analyses could be responsible for incompatibilities in binary mixtures (BMs) with HPMC and LAC, while temperature above 25 °C and presence of water were factors that promote incompatibilities in BMs with CCS and MgSTE. Overall results demonstrate that RA was compatible with MCC and PVP. Keywords: Rosmarinic acid, Excipient, Compatibility, TG, ssNMR, IST